Effect of using garlic oil on the production and composition of milk and some blood characteristics of Awassi Ewes - Ali, Wissam Jasim Mohammed; mohammed, Amar raeed; Ahmad, Wassem Khalid (Journal of agricultural, environmental and veterinary sciences, 2021)
This study was conducted in Beibocket area (8Km north of Mosul city) for the period 12-2-2019 to 13-4-2019. Fifteen Awassi ewes, with average 43.48 kg. aged (2-4years) is divided into three equal groups, (five ewes per group). Three groups were, feed relied on grazing fully. The first group was the control, the second group was given capsules 2 ml garlic oil/ewe/day. and the third group was given capsules of 4 ml garlic oil /ewe/day, respectively. The third group showed a significant increase (p<0.05) in milk Production compared to the second group and the control. Also, the third and second group showed a significant increase (p<0.05) in total and daily weights gain and final body weight compared to the control group. The results showed a significant decrease (p<0.05) for the second and third groups compared with control in milk fat%, cholesterol and triglycerides concentrations. There was no significant effect on White blood cell (WBC), red blood cells (RBC), haemoglobin, packed cell volume (PCV) concentration, non-fat soled% protein%, lactose% milk, Glucose, protein, Albumin, Globulin in serum blood as compared with control group. In general, the addition to the diet garlic oil could lead to improved body weight, Milk yield and some blood parameters of Awassi ewes.